Zoom: The luminous winters of Klavdij Sluban - Agnès Bardon (The UNESCO Courier, 2023)
It’s a story that began long ago, in another lifetime. Snow – sneg in Slovenian, the mother tongue of Klavdij Sluban – has marked the work of this traveling photographer for 25 years. Like a dotted line going back to his childhood, it connects him to Slovenia, his home country, which he left at eight years old.